2006
DOI: 10.1152/ajpregu.00556.2005
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal muscle activity during voiding in female rats with normal or irritated bladder

Abstract: Cruz, Yolanda, and John W. Downie. Abdominal muscle activity during voiding in female rats with normal or irritated bladder. Am J Physiol Regul Integr Comp Physiol 290: R1436 -R1445, 2006. First published December 22, 2005 doi:10.1152/ajpregu.00556.2005The aims of the present study were to determine in female rats whether abdominal muscle discharges during normal voiding and to describe the effect of bladder irritation on this visceromotor activity. The sensory pathway of this reflex was also determined. Ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 74 publications
4
42
0
1
Order By: Relevance
“…alone on various cystometric parameters and similar negative results have been reported in a conscious rat preparation. 23 Cruz and Downie 6 have shown that abdominal muscle contractions are present during spontaneous voiding and during voiding evoked by saline infusion within the physiological range of distending pressures in both conscious and urethane-anesthetized rats. It should, therefore, be acknowledged that the VMR utilized in the present study is not necessarily specific for nociceptive events, but this response does increase in a graded fashion to intensities of UBD that are above the non-painful, normal physiological range of intensities.…”
Section: Discussionmentioning
confidence: 99%
“…alone on various cystometric parameters and similar negative results have been reported in a conscious rat preparation. 23 Cruz and Downie 6 have shown that abdominal muscle contractions are present during spontaneous voiding and during voiding evoked by saline infusion within the physiological range of distending pressures in both conscious and urethane-anesthetized rats. It should, therefore, be acknowledged that the VMR utilized in the present study is not necessarily specific for nociceptive events, but this response does increase in a graded fashion to intensities of UBD that are above the non-painful, normal physiological range of intensities.…”
Section: Discussionmentioning
confidence: 99%
“…Although VMR and pressor responses elicited by colorectal (Ness and Gebhart, 1988), gastric (Ozaki et al, 2002), bladder (Ness et al, 2001;Cruz and Downie, 2006), and cervix (SandnerKiesling et al, 2002) distention have been well documented, studies of such responses to vaginal distention have not been done. Pseudoaffective responses likely would be elicited by these stimuli because they evoke behavioral escape responses Bradshaw et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to detrusor contraction and urine flow, rat voiding includes abdominal wall contraction 14 and an elevation in blood pressure (BP). 15 As abdominal wall contraction is a significant component of rat voiding, it has been termed the voiding-associated abdominal wall response (VAR).…”
Section: Introductionmentioning
confidence: 99%